Thrombin activates the p21-activated kinase in pulmonary artery smooth muscle cells. Role in tissue factor expression - Görlach, Agnes; BelAiba, Rachida S; Hess, John; Kietzmann, Thomas (Thrombosis and haemostasis, 2005)
The p21-activated serine/threonine kinases (PAK) play an important role in a variety of cellular functions. However, their role in the smooth muscle response to thrombin, which is activated upon vascular injury and promotes vascular remodelling processes, is not resolved. Here we investigated the role of PAK in thrombin signalling and regulation of tissue factor (TF), the activator of the extrinsic coagulation cascade, in pulmonary artery smooth muscle cells (PASMC), the main cell type responsible for vascular remodelling in pulmonary hypertension. PAK was rapidly phosphorylated in response to thrombin. Thrombin and active PAKT423E phosphorylated p38 MAP kinase (p38MAPK), ERK1/2, phosphatidylinositol-dependent kinase-1 (PDK1) and protein kinase B/Akt (PKB) whereas kinase-deficient PAK1 prevented activation of these kinases by thrombin. In addition, kinase- deficient MKK3 inhibited activation of PDK1 and PKB by thrombin. Further, thrombin and active PAK1 induced TF expression and promoter activity while kinase-deficient PAK1 diminished thrombin-induced TF upregulation. Moreover, kinase-deficient MKK3, PDK1 and PKB inhibited thrombin- and PAK-dependent TF expression and promoter activity. Together these findings show that PAK is a critical element of thrombin signalling in PASMC which is involved in the regulation of TF expression by sequentially activating MKK3/p38MAPK, PDK1 and PKB. Thus, PAK may play an important role in promoting vascular remodelling processes in pulmonary hypertension.